2016
DOI: 10.1134/s0040579516050080
|View full text |Cite
|
Sign up to set email alerts
|

Binary extraction of lanthanides (III) nitrates with carboxylates and dialkylphosphates of secondary and tertiary amines

Abstract: Abstract⎯The separation of lanthanide (III) ions with binary extractants based on carboxylates, di-(2-ethylhexyl)phosphates of secondary and tertiary amines and their mixtures has been studied. The parameters of lanthanide nitrates extraction from the aqueous phase by solutions of these substances in nonpolar diluents have been found to fit the binary extraction mechanism. For systems containing di-(2-ethylhexyl) phosphate and caprate of dioctylammonium and trioctylammonium, synergistic effects have been obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…It has been reported that the extraction of REEs by the binary extractants is improved in the presence of carboxylates due to the solvation of extracted species in the organic phase [43,44]. Thus, the mixture of Cyanex 272 with caprylic acid was examined to improve the solubility of lanthanum extracted complexes.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the extraction of REEs by the binary extractants is improved in the presence of carboxylates due to the solvation of extracted species in the organic phase [43,44]. Thus, the mixture of Cyanex 272 with caprylic acid was examined to improve the solubility of lanthanum extracted complexes.…”
Section: Introductionmentioning
confidence: 99%